Psychological interventions for depression among informal caregivers of older adult populations: protocol of a systematic review and meta-analysis of randomised controlled trials - Danelle Pettman; Louise von Essen; Oscar Blomberg; Joanne Woodford; Erika Mårtensson; Renita Sörensdotter (BMJ Open)
Introduction Increased life expectancy has led to an increased demand for family members to provide informal care for their older relatives in the home. Many studies suggest informal caregivers are at greater risk of experiencing symptoms of depression. However, there is a lack of research examining the effectiveness of psychological interventions targeting these symptoms alongside clinical and methodological moderators potentially associated with intervention effectiveness. This review aims to address this gap and will inform the development of a psychological intervention targeting depression among adult-child caregivers of older parents, given many studies show that among informal caregivers of older adults, adult children experience specific difficulties and needs for psychological support. Further, the lack of studies targeting adult children specifically necessitates conducting this review targeting caregivers of older adults in general.Methods and analysis Randomised controlled trials of psychological interventions targeting symptoms of depression among informal caregivers will be identified via a systematic search of electronic databases (PubMed, Cumulative Index to Nursing and Allied Health Literature, Excerpta Medica DataBase, PsycINFO, Cochrane Library and Web of Science) and supplemented by handsearching of previous systematic reviews, reference and forward citation checking, and expert contact. If possible, a meta-analysis will be conducted to examine the: (1) effectiveness of psychological interventions for depression among informal caregivers of older adults, (2) effectiveness of psychological interventions for secondary outcomes such as anxiety, stress, caregiver burden, psychological distress, quality of life, well-being and self-efficacy and (3) moderating effects of clinical and methodological factors on effectiveness.Ethics and dissemination Ethical approval will not be necessary for this study given primary data will not be collected. Results will inform the development of a psychological intervention for adult-child caregivers of older parents and will be disseminated through publication in peer-reviewed journals and conference presentations.PROSPERO registration number CRD42020157763.